Dorland's illustrated medical dictionary. - Dorland, W. A. Newman (Philadelphia, PA : Saunders, 2003)
The 30th Edition of the Dorland's medical dictionary features an all-new design with full-color, three-dimensional line art, color photography, and diagnostic and pathologic images. The New Edition features more than 125,000 terms, including over 3,000 new terms - over 800 related to complementary and alternative medicine - as well as improved and expanded appendices. An accompanying CD-ROM includes the Dorland's Spellchecker program.--Jacket
Keywords: Dictionaries; Medicine; Medicine